Parenchyma Abundance in Wood of Evergreen Trees Varies Independently of Nutrients - Kotowska, Martyna M.; Wright, Ian J.; Westoby, Mark (Frontiers in Plant Science, 2020)
The abundance of living cells in wood – mainly as interconnected axial and ray parenchyma networks – varies widely between species. However, the functional significance of this variation and its role in plant ecological strategies is poorly understood, as is the extent to which different parenchyma fraction are favoured in relation to soil nutrients and hydraulic functions. We analysed wood tissue fractions of 16 Australian angiosperm species sampled from two nearby areas with similar climate but very different soil nutrient profiles and investigated structure-function links with soil and tissue nutrient concentrations and other plant traits. We expected the variation in parenchyma fractions to influence nutrient concentrations in wood xylem, and to find species with lower parenchyma fractions and accordingly lower nutrient requirements on lower-nutrient soils. Surprisingly, both axial and ray parenchyma fractions were mostly unrelated to tissue and soil nutrient concentrations, except for nitrogen concentration in stem sapwood. Species from low nutrient soils showed higher fractional P translocation from both leaves and sapwood, but little patterning with respect to tissue nitrogen. While species from high and low nutrient soils clearly clustered along the soil-fertility axis, their tissue composition varied independently from plant functional traits related to construction costs and hydraulic anatomy. Our findings imply that there is considerable variation among species in the nutrient concentrations within different parenchyma tissues. The anatomical composition of wood tissue seems unrelated to plant nutrient requirements. Even though xylem parenchyma is involved in metabolic functions such as nutrient translocation and storage, parenchyma abundance on its own does not directly explain variation in these functions, even in co-occurring species. While parenchyma is highly abundant in wood of angiosperm trees, we are still lacking a convincing ecological interpretation of its variability and role in whole-tree nutrient budgets.